GAMBARAN TEMPER TANTRUM PADA ANAK TODDLER DI DESA MULIOREJO KEC. SUNGGAL KAB. DELI SERDANG TAHUN 2019 - Ernita Rante Rupang; Lindawati Simorangkir (STIKes Santa Elisabeth Medan, 2019)
Background: tantrums as a trick to fulfill their parents' needs and desires. The child vents his mistakes by rolling on the hard floor which can cause the child to be injured. Method: This type of research is a description with a cross sectional approach with the aim of seeing a picture of temper tantrums in toddlers in the village of Muliorejo, Kec. Sunggal Kab. Deli Serdang. The population in the study were all toddlers with a total of 40 respondents, the sampling technique in the study was the total sample. Measuring tool used is a questionnaireResults: Based on the results of the study, it was shown that the temper tantrums of toddlers were mostly mild, 20 people (60%), a small proportion of children's temper tantrums were severe, namely 4 people (10%).Conclusion: It is hoped that parents can understand and be able to communicate well with children